Consumption of sweetened-beverages and poverty in Colombia: when access is not an advantage - Oscar F. Herran; Gonzalo A. Patiño; Edna M. Gamboa (BMC, 2018)
Abstract Background This study characterizes the intake of sweetened beverages and establishes whether economic inequalities in their consumption exists. Methods Ecological study. Mixed methods using food frequency questionnaire and inequality indices. Based on the National Nutrition Survey, Colombia, 2010. The sweetened beverage intake of 17,514 subjects in 33 geodemographic units was estimated with a food frequency questionnaire and summarized. The calculation of inequality was based on the monetary poverty. The prevalence (yes/no) and frequency (times/day) of sweetened beverage consumption were estimated. Indices of economic inequality were calculated for both prevalence and frequency. Results The prevalence of sweetened beverage consumption was between 79.2% (95% CI, 75.7 to 82.8) in adults and 88.5% (95% CI, 85.8 to 91.3) in minors. The frequency of consumption in terms of times/day, was between 0.20 (95% CI, 0.16 to 0.24) in adults and 0.40 (95% CI, 0.33 to 0.46) in minors. The Gini coefficient for the prevalence was close to zero, between 0.04 and 0.08; for the frequency, it was slightly higher, between 0.12 and 0.25. Conclusions It was established that there is no economic inequality in the consumption of sweetened beverages. Consumption taxes could be regressive.